(untitled) (Nordic Journal of African Studies, 2009)
This paper focuses on the communicative use of allusive names among the Kabre of Northern Togo. The Kabre, like many other ethnic groups in Africa, have developed a verbal strategy that involves the use of personal names and animal names to indirectly communicate their feelings and opinions, particularly in conflict-laden situations. After providing a brief comparative analysis of African and Western concepts of proper names, the author presents a synopsis of the Kabre onomastic system and focuses on the category of allusive names which are used in the onomastic communication under consideration. He illustrates his analysis with examples from two subcategories of Kabre allusive names: the erotic names whose function is educational, and the polemical names which are vengeance-oriented.